Perbedaan Pengaruh Latihan Handgrip & Dumbell Terhadap Peningkatan Kekuatan Genggaman Jari Pada Pemain Bulu Tangkis - Novan Priambudi, Tegar Galih; Syaukani, Agam Akhmad (Jurnal Porkes, 2022)
This study was to determine the effect of handgrip and dumbbell exercises on increasing grip strength in badminton players. This type of research is quantitative research with experimental methods and the non-equivalent group design method. The sample of this study amounted to 20 respondents who were divided into 2 groups. Group 1 was given a handgrip exercise and group 2 was given a dumbbell exercise. The sampling technique used purposive sampling. The data analysis method used prerequisite test (normality test and homogeneity test) and hypothesis test using t test. Based on the results of the study, the average value of measurements before handgrip exercise was 33.19 and after handgrip exercise, the average value was 36.2 with an increase in value of 3.01. In the group that was given dumbbell training, before being given the exercise, the average value was 36.4 and after the exercise, the average value was 38.53 so that the average increased by 2.13. the results obtained tcount -1.1428 < ttable 1.8124 with an increase in the value of the exercise score before and after exercise in the handgrip group of 3.01 and in the dumbbell group of 2.13 so it was concluded that there was an insignificant effect between the group given the handrip exercise. as well as the group that was given dumbbell exercises. Handgrip exercises and dumbbell exercises have an effect on increasing the finger grip strength of badminton players